Review of Brandon LaBelle. 2010. Acoustic Territories: Sound Culture and Everyday Life. New York and London: Continuum - Fishbeck, Luke (Current Musicology, 2010)
Over the book’s course, LaBelle amply demonstrates how much about the acoustic paradigm can be read into this simple (silent) interaction: how sound- and listening- attaches us to one another and to our environments, and the ways in which these attachments are woven into the shared condition of the everyday. LaBelle intentionally blurs the already vague boundaries between “sound culture” and “sound art”. Acoustic Territories functions best as a proposal for a mode of listening, and that the consideration that “sounds begins and ends with noise”. In writing Acoustic Territories, LaBelle repositions sounds studies as radically engaged- a listening science with the potential reveal sound’s social materiality as it draws transformative meaning out of the background noise of the everyday.